1989
DOI: 10.1149/1.2097024
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanism for Low Voltage Cathodoluminescence of Sulfide Phosphors

Abstract: The degradation mechanism for the low voltage cathodoluminescence of normalZnS:normalZn and false(Zn0.22Cd0.78false)S:normalAg,normalCl phosphors in vacuum fluorescent displays has been investigated by mass spectrometer, field emission scanning electron microscope observation, Auger electron spectroscopy, and x‐ray photoelectron spectroscopy. It has been found that the decomposition and evaporation of phosphors take place during electron excitation. This causes the deterioration of cathode filaments as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(88 citation statements)
references
References 3 publications
0
86
1
1
Order By: Relevance
“…The luminescence degradation can occur via different mechanisms, such adsorption/desorption or charging at the surfaces, creation or activation of defects, etc. [25][26][27] . Although these intensity variations complicate the quantitative analysis of CL results, they can be used to investigate the lifetime of optoelectronic devices.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The luminescence degradation can occur via different mechanisms, such adsorption/desorption or charging at the surfaces, creation or activation of defects, etc. [25][26][27] . Although these intensity variations complicate the quantitative analysis of CL results, they can be used to investigate the lifetime of optoelectronic devices.…”
Section: Representative Resultsmentioning
confidence: 99%
“…On the other hand, although CL is an invaluable technique for qualitative characterization of optoelectronic materials, it also induces some cautions for quantitative measurements. Indeed, CL results depend not only on the excitation conditions, beam current and electron energy, but also on the amount of investigated materials 25 . Thus, a small variation of these parameters may significantly change the CL intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the different layers was attributed to the different background gas species present in the vacuum system during the degradation process. Itoh et al [14], using XPS (X-ray photoelectron spectroscopy), reported that ZnSO 4 was formed on the surface of the ZnS phosphor during electron irradiation in a H 2 O ambient. The ZnSO 4 formed in this case, however, was formed in dry oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Sebastian [10] observed a peak at -80 °C on the reference ZnS:Mn film, which was attributed to S interstitials. This peak was not observed on the ZnS:Cu,Au,Al phosphor powder, which means that the S interstitial could have probably resulted from the film growth process [14]. Structural defects such as dislocations and stacking faults formed in the ZnS films have also been reported to seriously affect the CL intensity within a distance of 200 nm from the interface [15].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a non-luminescent oxide layer, which is known to reduce the CL intensity of the CRT/FED phosphors, may form on the surface. For examples, it was demonstrated that when zinc sulfide (ZnS) based phosphors were exposed to a prolonged irradiation by energetic beam of electrons, the ZnS host dissociated into reactive ionic Zn 2+ and S 2-species, which in turn combined with ambient vacuum gases such as O 2 and H 2 O to form non-luminescent ZnO or ZnSO 4 layers or H 2 S gas (Swart el al., 1998;Itoh et al, 1989) as explained by the ESSCR model (Holloway et al, 1996(Holloway et al, , 2000. In the case of oxide based systems, the electron beam induced dissociation of atomic species is followed by desorption of oxygen from the surface.…”
Section: Cathodoluminescence Intensity Degradationmentioning
confidence: 99%